The mobile future - Parsons, D. (Massey University, 2004)
The computing power of a third generation mobile telephone is already similar to that of the first personal computers from the mid 1980s or a third generation minicomputer from the early 1970s. In addition, wireless connection speeds can be substantially faster than the fixed-line modem in most home computers. The fact that the mobile telephone is the standard tool, leisure device or fashion accessory (depending on your perspective) carried by millions worldwide means that the potential for these devices as a pervasive computing platform is huge. In the mobile future, service providers will be selling pervasive applications rather than handsets or bandwidth, and there will be many opportunities to develop new and innovative mobilised systems. This paper looks what the mobile future might hold, and explores some of the standards and tools that can be used for mobile application development. It asks some questions about what sort of applications might be developed and what kind of distributed architectures might be required to make them work effectively and efficiently. It concludes with a discussion of an application developed using the Java Technology for the Wireless Industry APIs that are being adopted by the major mobile providers.
Keywords: Mobile phones; Cellphones; Mobile application development; Wireless communication